Respuesta :

(7-4)=3 
(8-5)=3 
now we have 
2*3+6 / 3+3 
2*3 is 6 
now we have 
6+6/3+3 
12/6
2

Answer:

the simplified expression is 1/9

Step-by-step explanation:

The given expression is [tex]\frac{3^{-6}}{3^{-4}}[/tex]

We can apply the exponent law: [tex]\frac{x^a}{x^b}=a^{a-b}[/tex]

Applying this law, we get

[tex]\frac{3^{-6}}{3^{-4}}\\\\=3^{-6+4}\\\\=3^{-2}[/tex]

Now, apply the exponent rule:[tex]x^{-a}=\frac{1}{x^a}[/tex]

[tex]3^{-2}=\frac{1}{3^2}\\\\=\frac{1}{9}[/tex]

Hence, the simplified expression is 1/9